Penerapan Pendidikan Karakter Dalam Membentuk Sikap Sosial Peserta Didik Di SMP Negeri 2 Sungai Raya Kabupaten Kubu Raya - Vhicka Cantika; Sri Buwono; Thomy Sastra Atmaja; Maria Ulfah; Haris Firmansyah (Departement of Mathematics Education, 2024)
The research aims to examine the implementation of character education in shaping the social attitudes of students at SMP Negeri 2 Sungai Raya, Kubu Raya Regency. This study utilized a qualitative method with a descriptive approach, employing data collection techniques such as field observation and interviews. Primary data sources were utilized, and data collection instruments included mobile phones, interview guidelines, and observation guides. Data analysis techniques involved data reduction, data presentation, and drawing conclusions. To ensure data validity, the researcher employed source triangulation, technique triangulation, and time triangulation. The results indicate that at SMP Negeri 2 Sungai Raya, character education is implemented through various activities. Firstly, through routine activities such as flag ceremonies, community service, and religious activities including collective prayers and lectures for both Muslim and non-Muslim students. Secondly, through spontaneous activities involving providing advice on fighting, rude behavior, and offering assistance in certain situations. Thirdly, through conditioning activities by providing facilities, displaying slogans, implementing the school's vision and mission, and offering various extracurricular activities. Finally, through exemplary activities that promote cleanliness, provide healthy meals to students, and demonstrate exemplary behavior by all school staff, including the principal, teachers, administrative staff, library staff, and security personnel. All these activities aim to cultivate positive social attitudes and character traits in students, such as responsibility, discipline, cooperation, and empathy.